Study on Time-varying Friction Excitation and Meshing Efficiency of Helical Gears - Zhengbing Wang; Zhongming Liu; Lubing Shi; Xiaodan Huang; Xuefei Li (Jixie chuandong)
Based on the variation law of helical gear time-varying contact line length， an analytical algorithm of helical gear friction and friction torque is deduced. Based on the time-varying friction coefficient model， the influences of sliding friction on meshing force and meshing efficiency are studied. The results show that considering the sliding friction， the tooth surface meshing force is less than the normal force， the tooth surface meshing force increases with the increase of the rotating speed， decreases with the increase of tooth surface roughness and lubricating oil viscosity， and the influence is more significant in the multi-tooth meshing area. Under the action of time-varying friction coefficient， the average meshing efficiency increases with the increase of speed and torque， and decreases with the increase of tooth surface roughness， especially when the viscosity of the lubricating oil is large at low temperature.